ThreePenta flow design project / Ajmal Afiqah Mohd Hisham ... [et al.] - Mohd Hisham, Ajmal Afiqah; Hamdan, Nur Alya Saffiya; Muhamad Ali, Siti Nur Aisyah (2024)
Mostly constructed of timber and concrete, ThreePenta Flow is an open pavilion ideal for leisure, relaxation, and idea generation. We have seating areas indoors and outdoors for a group of people especially students to have discussions, work, or hang out. We target our UiTM students and staff, also open to the public. There are benches indoors and outdoors of the pavilion beside the pavilion. ThreePenta Flow is designed based on sustainability and eco-friendly concepts we combine this concept with hydroponic planting to make it more unique and can give benefits to others and the environment. There is a mini garden inside the center of the pavilion where plants and trees are planted. Students and staff also can go sightseeing besides the pavilion which we added a mini water pond and some plants.